INOVASI LAYANAN BERBASIS TEKNOLOGI INFORMASI PADA RUMAH SAKIT SEBAGAI BENTUK REFORMASI BIROKRASI - Arif Sofianto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2020)
One of the forms of bureaucratic reform in public services is to improve the quality of services, faster, cheaper, easier, and higher quality. In the health sector, hospitals owned by the Government of Central Java Province have developed electronic-based services. The purpose of this study is to describe the implementation of information technology-based services, identify supporting and inhibiting factors, and identify the contribution of information technology use to bureaucratic reform. This research is descriptive with a qualitative approach. Research subjects were 7 hospitals owned by the Government of Central Java Province. The informant is the manager of hospital services as well as the maker of the system application. Data analysis techniques using the model of Miles and Huberman, the collection, processing and presentation of data simultaneously. The conclusions of this study are: 1) Information technology-based services develop according to their capacities and resources Systems built independently are more developed and sustainable, and are low cost. 2) Supporting factors are good work culture, commitment, education, professionalism, responsibility, egalitarian, transparent and constructive. Internal barriers in the form of commitment, competence, and facilities. External barriers are accessibility and lack of public understanding. 3) The contribution of information technology-based services is speed of service, certainty of waiting time, transparency, and fairness. Benefits for hospitals improve work efficiency, speed and ease in providing services.